Pattern of family dynamics and treatment-seeking behaviour of caregivers of under-five children with uncomplicated malaria in a tertiary hospital in Ilesa, southwestern Nigeria - Abdulwasiu Akanfe Adegboyega; Abdulakeem Ayanleye Ahmed; Ibrahim Sebutu Bello; Olanrewaju Oloyede Oyegbade; Samuel Ademola Adegoke; Olufemi M. Olubiyi; Temitope Oluwafemi Olajubu; Kolawole Muideen Adewumi; Fatima Adenike Adegoke; Abraham Busola Oluwajuyitan (PLoS ONE, 2026)
Background The morbidity and possible consequent mortality resulting from malaria in children are either due to delayed treatment-seeking or preceded by an inappropriate treatment-seeking process. This study aimed to assess the relationship between the pattern of family dynamics and treatment-seeking behaviour of caregivers of under-five children with uncomplicated malaria. Methods This was a hospital-based cross-sectional study that recruited 350 child-caregiver pairs. An interviewer-administered questionnaire was used for data collection, and it was analysed using the Statistical Package for the Social Sciences (SPSS) software version 25. A p-value of < 0.05 was taken as statistically significant. Results The family dynamics of the caregivers revealed that 82.3% of them had strong family support, four-fifths (80.3%) had functional families, and a little over half of them (58.3%) had monthly family incomes that fell below the defined household poverty line. Only 41.7% of the caregivers had appropriate treatment-seeking behaviour. Caregivers from lower-income families had 2.5 times higher odds of exhibiting inappropriate treatment-seeking behaviour compared to those from higher-income families (OR, 2.494; 95% CI, 1.486–4.184; p = 0.001). Caregivers with dysfunctional families were about four times more likely to have inappropriate treatment-seeking behaviour compared to their counterparts with functional families (OR, 3.766; 95% CI, 1.445–9.813, p = 0.007). Conclusion Significant inappropriate treatment-seeking behaviour existed among caregivers of under-five children with uncomplicated malaria. Family factors related to inappropriate treatment-seeking behaviour were family income and family functioning. Strengthening the family and counselling on appropriate treatment-seeking is crucial to reducing malaria morbidity and mortality among under-five children.